Aplicação do modelo DPSIR na bacia hidrográfica do Rio Guaribas, Ceará, Brasil: subsídios para gestão ambiental local - Landim Neto, Francisco Otávio (2013)
The planning and environmental management within a watershed are needed to establish the appropriate use of natural resources. From this, it is emphasized the importance of studies that gather and discuss the aspects of natural, economic and social dynamics that influence the environmental unit. In effect, it was done the environmental diagnosis of river basin of Guaribas, west coast of Ceará, Northeast of Brazil, with the application of indicators of DPSIR model (Driving Forces, Pressures, State, Impact, Responses). Among the specific objectives are: (i) identify the main environmental problems affecting the population that inhabits the river basin of Guaribas, (ii) analyze the set of indicators of the DPSIR framework as a tool to support decision making in context of public policy, (iii) identify the actions needed to solve the environmental problems found in the study area. The theoretical and methodological framework was founded on DPSIR conceptual model, developed by the Organization for Economic Cooperation and Development in 2002. The above model focuses on the analysis of the ecosystemic and anthropogenic relationships embedded in the environmental systems present in the study area. Thus, the research provided an integrated analysis of environmental problems in relation to the causes that produce them, and even included the answers understood as purposeful actions that can be fostered and developed by government, civil society and economic sectors. It is understood that the appropriation of space in the study area occurs as a result of the urbanization process, the facilities of the port complex and the use of natural resources, attracted by the policy of state economic development state that, when conflict with the traditional communities, shows an uneven distribution of uses of coastal space. Thus, it was possible to say that the applicability of the DPSIR model was of great importance because it provided an integrated analysis of environmental problems, which still included the purposeful actions that can be fostered by government, civil society and economic sectors. It is considered that there is urgent need for discipline in the use of coastal environments present in the western sector of the State of Ceará.